Lipomatous nevus - Tagliavanti, M. (European Journal of Pediatric Dermatology, 2015)
In addition to the classical form of cerebriform, plaque lipomatous nevus, characterized by early-onset, segmental distribution and usually localized level with the pelvic girdle, there is isolated lipomatous nevus, presenting as a lump covered by normal skin, which is localized everywhere and becomes evident after the second decade of life. Our case is atypical, because it is localized to the buttock as the classic cerebriform form, started late and consisted of three distinct nodules. Histologically lipomatous nevus and subcutaneous adipose tissue can be distinguished because in lipomatous nevus the ectopic adipocytes are located in the dermis, often separated by a collagen band from subcutaneous fat and are not organized in lobules; lipomatous nevus differs from lipoma because the ectopic adipocytes in the dermis infiltrate between the collagen bundles around the vessels and sweat glands and do not have a capsule.